2022
DOI: 10.3390/nu14142789
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic Changes of Gut Microbiota following Treatment of Helicobacter pylori Infection with a Simplified Low-Dose Quadruple Therapy with Bismuth or Lactobacillus reuteri

Abstract: Background: Probiotic supplementation to antibiotic regimens against Helicobacter pylori infection has been proposed to improve eradication rate and to decrease detrimental effects on gut microbiota. Aims: To evaluate microbiota modifications due to a low-dose quadruple therapy with bismuth or Lactobacillus reuteri. Methods: Forty-six patients infected with H. pylori were prospectively enrolled in a single-centre, randomized controlled trial to receive b.i.d. with meals for 10 days low-dose quadruple therapy c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…These data confirm and extend the dynamics observed in a slightly larger cohort of patients (including those analyzed in this work) in our recent study based on 16S rRNA gene amplicon sequencing. 9 Specifically, in both studies we consistently found an increase in Proteobacteria, Lactobacillales, and Enterococcus following therapy. However, compared to the metaproteomics data, 16S rRNA gene sequencing enabled us to detect a larger number of genera reduced at T1 compared to T0.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…These data confirm and extend the dynamics observed in a slightly larger cohort of patients (including those analyzed in this work) in our recent study based on 16S rRNA gene amplicon sequencing. 9 Specifically, in both studies we consistently found an increase in Proteobacteria, Lactobacillales, and Enterococcus following therapy. However, compared to the metaproteomics data, 16S rRNA gene sequencing enabled us to detect a larger number of genera reduced at T1 compared to T0.…”
Section: Discussionmentioning
confidence: 58%
“…Nineteen adult patients diagnosed with H. pylori infection were recruited at the Department of Internal Medicine, Gastroenterology section, University of Sassari, Italy, in the context of a larger study described elsewhere. 9 Patients were defined as positive for H. pylori infection based on its detection in gastric specimens and/or a positive 13 C-Urea Breath Test 13 C-UBT) and/or a positive stool antigen test. The exclusion criteria were as follows: pregnancy or lactation, clinically significant diseases, recent gastroenteritis or bowel preparation for colonoscopy, history of drug or alcohol abuse, and use of antibiotics or probiotics within the month preceding the enrollment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fecal samples used in this study were obtained as part of a larger collaborative study ( 27 ) that was approved by the Institutional Review Board of the local Ethics Committee (ASL n. 1 Sassari, Prot. No.…”
Section: Methodsmentioning
confidence: 99%